Marathi Translation and Linguistic Validation of an Updated European Organization for Research and Treatment of Cancer Quality of Life Module for Head and Neck - Waghmare, Chaitali M.; Pawar, Hemant J.; Jain, Vandana S.; Bhanu, Arya; Thakur, Pradeep K.; Nirmal, Padmini H. (South Asian Journal of Cancer, 2020)
Aim This study was aimed to translate an updated European Organization for Research and Treatment of Cancer (EORTC) quality of life module for head and neck (EORTC QLQ-H&N43) in grammatically and conceptually acceptable Marathi language and its linguistic validation.Materials and Methods Approval was obtained from the Institutional Ethics Committee. The permission for translation was obtained from the EORTC translation unit (TU). The EORTC guidelines for the translation were followed to form a translation for pilot testing which was administered to 10 Marathi speaking head and neck squamous cell cancer (HNSCC) patients who gave informed written consent for the participation in the study. Patients were interviewed personally. The final Marathi translation was prepared and sent to EORTC TU for approval. Statistical analysis was performed using SYSTAT version 12 by Cranes software, Bengaluru, Karnataka, India.Results After getting permission, the translation files were received from EORTC TU, including Marathi EORTC QLQ-H&N35 for reference. Two forward translations, reconciled translation, back translations, first interim translation, translation for proof editing, and second interim translation (SIT) were prepared. This SIT was pilot tested in 10 Marathi-speaking HNSCC patients. Each patient was interviewed regarding difficulty in answering, confusing or offensive word, and reframing sentence. The questionnaire was well understood by patients reflecting its linguistic validity. After incorporating the changes as per the patient’s interview, updated translation was prepared and sent to EORTC TU which was accepted and approved by EORTC. The psychometric analysis of pilot testing showed that the questionnaire is acceptable.Conclusion Marathi translation of EORTC QLQ-H&N43 is well accepted and understandable. It can be used for future studies.
Keywords: European Organization for Research and Treatment of Cancer QLQ-H&N43; head and neck cancer; Marathi translation; quality of life